Modeling Goodwill for Banks: A Residual Income Approach with Empirical Tests* - Begley, Joy; Chamberlain, Sandra L.; Li, Yinghua (Contemporary Accounting Research, 2006)
Abstract This paper uses the residual income valuation technique outlined in Feltham and Ohlson 1996 to examine the relation between stock valuations and accounting numbers for a prototypical banking firm. Prior work of this nature typically assumes a manufacturing setting. This paper contributes to the prior research by clarifying how the approach can be extended to settings where value is created from financial assets and liabilities. Key elements of our model include allowing banks to generate positive net present value from either lending or borrowing activities, and allowing for accounting policy to affect valuation through the loan loss allowance. We validate our model using archival data analysis, and interpret coefficients in light of our modeling assumptions. These results suggest that banks create value more from deposit‐taking activities than from lending activities. Vuong tests confirm that our model outperforms adaptations of the unbiased accounting model of Ohlson 1995 and adaptations of the base model proposed by Beaver, Eger, Ryan, and Wolfson 1989. However, our model is outperformed by the popular net income‐book value model used in many empirical studies, and we can formally reject one of our key modeling assumptions. These tests of our model suggest future avenues for improving upon the theoretical analysis.